Accounting : A Framework for Decision Making - Jackling [et al.] (Sydney McGraw-Hill Education, 2010)
Thoroughly updated and re-sequenced in response to market feedback, Accounting: A Framework for Decision Making is an ideal first year accounting principles text. Presented in a straightforward style, the third edition focuses on key concepts and illustrates each concept with clear graphical or textual explanations and examples. The latest AASB standards and accounting techniques underpin the content throughout and new and revised questions have been added to the end of chapter material. With an accessible technical focus, Accounting: A Framework for Decision Making has a clear and broad content structure that means the book lends itself to both majors and non-majors courses
Includes Appendix, Colored Illustrations and Bibliography.
Keywords: Accounting -- Textbooks